Sales volume analysis through trust in manufacturing companies: Study on dynamix cement consumers - Santosa, Djoko; Hadi, Prasetyo; Astuti, Miguna; Manggabarani, Alfatih Sikki (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Purpose – The purpose of this study is to find out and analyze whether trust, country of origin, brand image, and product quality influences sales volume both directly and indirectly through trust on consumers of Semen Dynamix in Indonesia.Design/methodology/approach – A quantitative approach was used with purposive sampling to select 210 respondents meeting the research criteria. Data were analyzed using the Structural Equation Modeling (SEM) method with the SmartPLS tool.Findings – The results show that country of origin, brand image, and product quality significantly influence sales volume, while the influence of country of origin is not statistically significant. Trust serves as a mediating factor in the indirect relationships between these variables and sales volume.Research limitations/implications – The limitation of this study is its sole focus on Semen Dynamix, which may restrict the generalizability of the findings. Future research could explore additional factors or apply similar methods across other product categories.Practical implications – The study suggests that enhancing trust by improving country of origin perceptions, brand image, and product quality can positively affect sales. Practical applications include marketing strategies that highlight these attributes to strengthen customer trust and, in turn, drive sales volume.Originality/value – This study offers a fresh perspective on trust, highlighting its active role in mediating the effects of brand-related factors on sales. Insights from this research can guide marketers and practitioners in developing brand and sales-oriented strategies.